Legal Certainty and Investment Protection in Indonesian Start-up Companies - Glen Charlie Karo Sekali; Mahmul Siregar; Joiverdia (Talenta Publisher, 2026)
The rapid growth of start-up companies in Indonesia has strengthened the digital economy and increased investment opportunities. However, the legal framework governing start-ups remains fragmented and has not fully addressed their unique business characteristics. This study aims to analyze the legal framework governing start-ups in Indonesia, evaluate policies on domestic and foreign ownership, and assess the role of law in supporting investment. The research employs a normative juridical method using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed qualitatively. The study finds that Indonesian regulations do not yet provide a specific legal regime for start-ups, resulting in legal uncertainty regarding corporate governance and investment arrangements. Although the Online Single Submission (OSS) system has simplified business licensing, regulatory ambiguities concerning foreign ownership persist in several digital business sectors. These conditions may affect investment certainty and the long-term sustainability of start-up businesses. The novelty of this study lies in proposing an integrated legal-regulatory approach that balances investment facilitation, ownership governance, and the protection of national economic interests. This study contributes to the development of business law by providing a framework for improving legal certainty and strengthening investment policies in Indonesia’s digital economy.